2021
DOI: 10.1021/acs.bioconjchem.1c00408
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Modulated Catalytic Selectivity of Ag Clusterzyme for Relieving Multiorgan Injury via Inhabiting Acute Oxidative Stress

Abstract: The artificial enzymes at the atomic level have shown great potential in chemical biology and nanomedicine, and modulation of catalytic selectivity is also critical to the application of nanozymes. In this work, atomic precision Ag25 clusterzymes protected by single- and dual-ligand were developed. Further, the catalytic activity and selectivity of Ag25 clusterzymes were modulated by adjusting doping elements and ligand. The Ag24Pt1 shows more prominent antioxidant activity characteristics in the dual-ligand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Second, biocompatibility is important for the development of neuron devices. An electrode can be modified with nanomaterials possessing high catalytic activity, such as nanoclusters 114,[119][120][121][122][123] , atomic level nanozymes 122,[124][125][126][127][128][129] and two-dimensional materials [130][131][132][133] , to reduce the inflammatory response of neural tissue. Third, integrated neuron devices can be developed to achieve multiple functions simultaneously [134][135][136] .…”
Section: Discussionmentioning
confidence: 99%
“…Second, biocompatibility is important for the development of neuron devices. An electrode can be modified with nanomaterials possessing high catalytic activity, such as nanoclusters 114,[119][120][121][122][123] , atomic level nanozymes 122,[124][125][126][127][128][129] and two-dimensional materials [130][131][132][133] , to reduce the inflammatory response of neural tissue. Third, integrated neuron devices can be developed to achieve multiple functions simultaneously [134][135][136] .…”
Section: Discussionmentioning
confidence: 99%
“…[146] Ag 25 MHA 18 showed a similar increase in antioxidant ability after single-atom substitution and dual-ligand protection compared to Ag 24 Pt 1 (MHA/MPA) 18 and Ag 24 Cu 1 (MHA) 18 , indicating modulated catalytic selectivity. [147] Recently, metal NCs were reported to act as monoamine oxidase B inhibitors (MAOI), which paved the way for creating a more effective drug for Alzheimer's disease. [142] The Au NCs and enzymatic substrates exhibit competitive relationships.…”
Section: Biocatalystsmentioning
confidence: 99%
“…[ 146 ] Ag 25 MHA 18 showed a similar increase in antioxidant ability after single‐atom substitution and dual‐ligand protection compared to Ag 24 Pt 1 (MHA/MPA) 18 and Ag 24 Cu 1 (MHA) 18 , indicating modulated catalytic selectivity. [ 147 ]…”
Section: Bioresponses At the Cellular Levelmentioning
confidence: 99%
“…Fortunately, recent studies have shown that some nanomaterials that can reduce oxidation by denaturation in the cellular microenvironment act as bioenzymes to eliminate excessive intracellular ROS. [ 15 ] Nanozyme, a type of nanomaterial that possesses intrinsic enzyme‐like activity, catalyzes enzyme substrates efficiently under mild conditions and exhibits catalytic efficiency and enzymatic reaction kinetics similar to those of natural enzymes. [ 16 ] Compared with bioenzymes, nanozymes still maintain 85% catalytic activity even in strong acids/bases (pH ≈2–10) or over a wide temperature range (≈4–90 °C), which suggests broad clinical application prospects.…”
Section: Introductionmentioning
confidence: 99%